An Experimental Study on Plastic Blended Bituminous Concrete Mix Roads - Sarada, T.; Sreeja, G. (International Journal of Engineering and Technology, 2018)
In this new era there are lot of changes are onaerved.But new materials and practices are not coming out that much. Some of the people uses some partial replacement of bitumen and tar which gives some satisfactory results. But later investigations prove that all those materials are not exhibits required properties in all aspects. In that time investigators turn their eye on the recycling materials like rubber and plastic. They noticed that both materials gives the satisfactory results. On the other hand the usage of plastic (polyethylene bags, pet bottles, polystyrene and other plastic products) products increases day by day, that leads to lot of pollution due to plastic waste. This plastic material takes hundreds of years to decompose in the soil. Hence they become complicated to environment. This plastic waste stops the percolations of rain water in to the soil and affects the drainage property of soil. It also damages the soil fertility.A new technology introduced to usages of plastic waste in bitumen to strengthen the bituminous concrete mix and increase the load bearing strength. It will help to reduce the waste plastic content and also make the pavement more durable and strong, economical alsoÂ
Keywords: polyethelene; marshall stability; Bitumen.